Những câu hỏi liên quan
LP
Xem chi tiết
TN
Xem chi tiết
NT
28 tháng 8 2021 lúc 21:57

3: Ta có: \(\sqrt{4x+1}=x+1\)

\(\Leftrightarrow x^2+2x+1=4x+1\)

\(\Leftrightarrow x\left(x-2\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\left(nhận\right)\\x=2\left(nhận\right)\end{matrix}\right.\)

4: Ta có: \(2\sqrt{x-1}+\dfrac{1}{3}\sqrt{9x-9}=15\)

\(\Leftrightarrow3\sqrt{x-1}=15\)

\(\Leftrightarrow x-1=25\)

hay x=26

5: Ta có: \(\sqrt{4x^2-12x+9}=7\)

\(\Leftrightarrow\left|2x-3\right|=7\)

\(\Leftrightarrow\left[{}\begin{matrix}2x-3=7\\2x-3=-7\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=10\\2x=-4\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=5\\x=-2\end{matrix}\right.\)

Bình luận (0)
HL
Xem chi tiết
NT
17 tháng 12 2023 lúc 20:27

a: ĐKXĐ: \(x\in R\)

\(\sqrt{\left(2x+3\right)^2}=5\)

=>|2x+3|=5

=>\(\left[{}\begin{matrix}2x+3=5\\2x+3=-5\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=2\\2x=-8\end{matrix}\right.\)

=>\(\left[{}\begin{matrix}x=1\left(nhận\right)\\x=-4\left(nhận\right)\end{matrix}\right.\)

b: ĐKXĐ: \(x\in R\)

\(\sqrt{9\left(x-2\right)^2}=18\)

=>\(\sqrt{9}\cdot\sqrt{\left(x-2\right)^2}=18\)

=>\(3\cdot\left|x-2\right|=18\)

=>\(\left|x-2\right|=6\)

=>\(\left[{}\begin{matrix}x-2=6\\x-2=-6\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=8\left(nhận\right)\\x=-4\left(nhận\right)\end{matrix}\right.\)
c: ĐKXĐ: x>=2

\(\sqrt{9x-18}-\sqrt{4x-8}+3\sqrt{x-2}=40\)

=>\(3\sqrt{x-2}-2\sqrt{x-2}+3\sqrt{x-2}=40\)

=>\(4\sqrt{x-2}=40\)

=>\(\sqrt{x-2}=10\)

=>x-2=100

=>x=102(nhận)

d: ĐKXĐ: \(x\in R\)

\(\sqrt{4\left(x-3\right)^2}=8\)

=>\(\sqrt{\left(2x-6\right)^2}=8\)

=>|2x-6|=8

=>\(\left[{}\begin{matrix}2x-6=8\\2x-6=-8\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=14\\2x=-2\end{matrix}\right.\)

=>\(\left[{}\begin{matrix}x=7\left(nhận\right)\\x=-1\left(nhận\right)\end{matrix}\right.\)

e: ĐKXĐ: \(x\in R\)

\(\sqrt{4x^2+12x+9}=5\)

=>\(\sqrt{\left(2x\right)^2+2\cdot2x\cdot3+3^2}=5\)

=>\(\sqrt{\left(2x+3\right)^2}=5\)

=>|2x+3|=5

=>\(\left[{}\begin{matrix}2x+3=5\\2x+3=-5\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x=2\\2x=-8\end{matrix}\right.\)

=>\(\left[{}\begin{matrix}x=1\left(nhận\right)\\x=-4\left(nhận\right)\end{matrix}\right.\)

f: ĐKXĐ:x>=6/5

\(\sqrt{5x-6}-3=0\)

=>\(\sqrt{5x-6}=3\)

=>\(5x-6=3^2=9\)

=>5x=6+9=15

=>x=15/5=3(nhận)

Bình luận (0)
TN
Xem chi tiết
NT
20 tháng 5 2022 lúc 19:00

Câu 1: 

\(A=\sqrt{3}+\sqrt{2}-\sqrt{3}+\sqrt{2}=2\sqrt{2}\)

Câu 2: 

\(\Leftrightarrow\left|2x-3\right|=\sqrt{3}+\sqrt{2}-\sqrt{3}+\sqrt{2}=2\sqrt{3}\)

\(\Leftrightarrow\left[{}\begin{matrix}2x-3=2\sqrt{3}\\2x-3=-2\sqrt{3}\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2\sqrt{3}+3}{2}\\x=\dfrac{-2\sqrt{3}+3}{2}\end{matrix}\right.\)

Bình luận (0)
H24
20 tháng 5 2022 lúc 19:02

`1)A=\sqrt{5+2\sqrt{6}}-\sqrt{5-2\sqrt{6}}`

   `A=\sqrt{3+2\sqrt{3}.\sqrt{2}+2}-\sqrt{3-2\sqrt{3}.\sqrt{2}+2}`

  `A=\sqrt{(\sqrt{3}+\sqrt{2})^2}-\sqrt{(\sqrt{3}-\sqrt{2})^2}`

  `A=|\sqrt{3}+\sqrt{2}|-|\sqrt{3}-\sqrt{2}|`

  `A=\sqrt{3}+\sqrt{2}-\sqrt{3}+\sqrt{2}=2\sqrt{2}`

_________________________________________________

`2)\sqrt{4x^2-12x+9}=\sqrt{5+2\sqrt{6}}-\sqrt{5-2\sqrt{6}}`  

`<=>\sqrt{4x^2-12x+9}=2\sqrt{2}` (Như câu `1`)

`<=>4x^2-12x+9=8`

`<=>4x^2-12x+1=0`

Ptr có:`\Delta'=(-6)^2-4=32 > 0`

`=>` Ptr có `2` nghiệm pb

`x_1=[-b+\sqrt{\Delta'}]/a=[-(-6)+\sqrt{32}]/4=[3+2\sqrt{2}]/2`

`x_2=[-b-\sqrt{\Delta'}]/a=[-(-6)-\sqrt{32}]/4=[3-2\sqrt{2}]/2`

Vậy `S={[3+-2\sqrt{2}]/2}`

Bình luận (0)
NT
20 tháng 5 2022 lúc 19:02
Bình luận (0)
H24
Xem chi tiết
VT
24 tháng 9 2023 lúc 19:26

`a, <=> 5/3 . 3sqrt(x^2+2) + 3/2.2sqrt(x^2+2)-7sqrt6=sqrt(x^2+2)`

`= (5+3-1)sqrt(x^2+2)=7sqrt6`

`<=> 7sqrt(x^2+2)=7sqrt6`.

`<=> x^2+2=36`.

`<=> x^2=34`.

`<=> x=+-sqrt(34)`.

Vậy...

`b, sqrt(4x^2-12x+9)-6=0`

`<=> |2x-3|=6`.

`@ x >=3/2 <=> 2x-3=6.`

`<=> x=9/2 (tm)`.

`@x <3/2 <=> 3-2x=6`

`<=> 2x=-3`

`<=> x=-3/2.`

Vậy...

Bình luận (0)
PH
Xem chi tiết
TN
13 tháng 1 2017 lúc 21:31

Bài 1: \(\sqrt{x^2+2x+5}=\sqrt{\left(x^2+2x+1\right)+4}\)

\(=\sqrt{\left(x+1\right)^2+4}\ge\sqrt{4}=2\)

Dấu "=" xảy ra khi \(x=-1\)

Vậy...

Bài 2:

\(\sqrt{4x^2-4x+1}+\sqrt{4x^2-12x+9}\)

\(=\sqrt{\left(2x-1\right)^2}+\sqrt{\left(2x-3\right)^2}\)

\(=\left|2x-1\right|+\left|2x-3\right|\)\(=\left|2x-1\right|+\left|3-2x\right|\)

\(\ge\left|2x-1+3-2x\right|=2\)

Dấu "=" xảy ra khi \(\frac{1}{2}\le x\le\frac{3}{2}\)

Vạy....

Bình luận (0)
BG
Xem chi tiết
LH
26 tháng 7 2021 lúc 16:34

\(A=\sqrt{4x^2-4x+1}+\sqrt{4x^2-12x+9}\)

\(=\sqrt{\left(2x-1\right)^2}+\sqrt{\left(2x-3\right)^2}=\left|2x-1\right|+\left|2x-3\right|=\left|2x-1\right|+\left|3-2x\right|\ge\left|2x-1+3-2x\right|=2\)

\(\Rightarrow A\ge2\)

Dấu "=" xảy ra khi \(\left(2x-1\right)\left(3-2x\right)\ge0\)

\(\Leftrightarrow\dfrac{1}{2}\le x\le\dfrac{3}{2}\)

Bình luận (0)
PS
Xem chi tiết
KN
Xem chi tiết
GH
2 tháng 7 2023 lúc 8:44

1

ĐK: \(x\in R\)

\(\sqrt{x^2-4x+4}=\sqrt{4x^2-12+9}\\ \Leftrightarrow\sqrt{\left(x-2\right)^2}=\sqrt{\left(2x-3\right)^2}\\ \Leftrightarrow\left|x-2\right|=\left|2x-3\right|\\ \Leftrightarrow\left[{}\begin{matrix}x-2=2x-3\\2-x=2x-3\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=1\\x=\dfrac{5}{3}\end{matrix}\right.\)

2

ĐK: \(\left\{{}\begin{matrix}x+2\sqrt{x-1}\ge0\\x-1\ge0\end{matrix}\right.\Leftrightarrow x\ge1\)

Đặt \(t=\sqrt{x-1}\left(t\ge0\right)\Rightarrow t^2=x-1\Rightarrow x=t^2+1\)

\(\sqrt{x+2\sqrt{x-1}}=2\\ \Leftrightarrow\sqrt{t^2+2t+1}=2\\ \Leftrightarrow\sqrt{\left(t+1\right)^2}=2\left(1\right)\)

Do có \(t\ge0\) nên \(\left(1\right)\Leftrightarrow t+1=2\Leftrightarrow t=2-1=1\)

\(\Rightarrow x=t^2+1=1^2+1=2\) (thỏa mãn)

Bình luận (0)
NT
2 tháng 7 2023 lúc 8:32

1: =>|2x-3|=|x-2|

=>2x-3=x-2 hoặc 2x-3=-x+2

=>x=1 hoặc 3x=5

=>x=5/3 hoặc x=1

2: \(\Leftrightarrow\left|\sqrt{x-1}+1\right|=2\)

=>căn x-1+1=2

=>căn x-1=1

=>x-1=1

=>x=2

Bình luận (0)